Public Debt and the Future of the EU's Stability and Growth Pact - Heinz-Dieter Wenzel; Jörg Lackenbauer; Klaus J. Brösamle (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2004)
Monetary policy and fiscal policy are connected in various ways. This is why the adoption of the Euro as a common European currency has been accompanied by the setup of the European Union's Stability and Growth Pact, a framework for the coordination of the EU countries' fiscal policies. In this paper, we provide a short overview of the SGP's history of origins and the degree to which the EU Member States adhered to it. Further, we analyse what effects public debt and public deficits have and whether, after all, public debt should be limited in one way or the other. Along these lines, the case for budgetary policy coordination in the special context of the Economic and Monetary Union is presented. After looking at the current SGP framework, we shed light on its main shortcomings and present various reform proposals, all of which are critically questioned. Finally, we present a case for a more flexible country-by-country approach to the interpretation of the deficit criterion (based on some simple algebra).
Keywords: H87; E61; D62; H6; E62; 330; Stability and Growth Pact (SGP); public debt; public deficits; fiscal policy; policy coordination; Maastricht criteria; EU-Stabilitätspakt; Reform; Öffentliche Schulden; Haushaltsdefizit; Internationale wirtschaftspolitische Koordination; EU-Staaten